Noninvasive molecular imaging of small living subjects using Raman spectroscopy - Keren, S; Zavaleta, C; Cheng, Z; de la Zerda, A; Gheysens, O; Gambhir, S S (Proceedings of the National Academy of Sciences - PNAS, 2008)
Molecular imaging of living subjects continues to rapidly evolve with bioluminescence and fluorescence strategies, in particular being frequently used for small-animal models. This article presents noninvasive deep-tissue molecular images in a living subject with the use of Raman spectroscopy. We describe a strategy for small-animal optical imaging based on Raman spectroscopy and Raman nanoparticles. Surface-enhanced Raman scattering nanoparticles and single-wall carbon nanotubes were used to demonstrate whole-body Raman imaging, nanoparticle pharmacokinetics, multiplexing, and in vivo tumor targeting, using an imaging system adapted for small-animal Raman imaging. The imaging modality reported here holds significant potential as a strategy for biomedical imaging of living subjects.